Pengaruh pengawasan dan kompetensi terhadap kinerja karyawan pada Hotel Permai Pekanbaru - Akbar, Rabiaful; Sasmita, Jumiati; Hamid, Liswar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to determine how the effect of supervision and competence variables simultaneously and partially on the performance of employees at Permai Hotel Pekanbaru. As for the sample in this study were employees of Hotel Permai Pekanbaru with a sample of 50 people and all populations sampled in this study . Data analysis using descriptive analysis , but it is also a quantitative analysis that is using multiple linear regression with SPSS ( Services For Product and Solution Statistics ) version 20. From the results of the testing that has been done, simultaneous regression test (F-test) showed that the supervision and competence simultaneously affect the performance of employees. Partial Test Results (t test) showed that the control variable is partially significant effect on employee performance, and competence variables partially significant effect on employee performance means better supervision and competence of the employees will be able to affect the performance of Hotel Permai. From the test results R square is known that the influence of the Performance Monitoring and Competence Permai Hotel employees by 70.1% and the rest is influenced by other variables not examined.Keywords : Supervision, Competency and Performance